A combination of two conjugate gradient methods under a new line search with its application in image restoration problems - Maiza, Asma; Ziadi, Raouf; Saleh, Mohammed A.; Almaymuni, Abdulgader Z. (Zielona Góra: Uniwersytet Zielonogórski)
A combined conjugate gradient algorithm is introduced for solving unconstrained optimization problems. In the suggested approach, the conjugate gradient parameter is defined as a combination of PRP (Polak-Ribiére-Polyak) and BRB (Rahali- Belloufi-Benzine) conjugate gradient parameters. To improve the convergence properties, we have adopted a new inexact line search technique that fits in with the suggested approach. The proposed line search technique can be useful for other gradient descent methods.
Keywords: unconstrained optimization; conjugate gradient methods; inexact line search; global convergence; image processing